2014
DOI: 10.1136/jfprhc-2013-100784
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy desire and dual method contraceptive use among people living with HIV attending clinical care in Kenya, Namibia and Tanzania

Abstract: Aim To describe factors associated with pregnancy desire and dual method use among people living with HIV in clinical care in sub-Saharan Africa. Design Sexually active HIV-positive adults were enrolled in 18 HIV clinics in Kenya, Namibia and Tanzania. Demographic, clinical and reproductive health data were captured by interview and medical record abstraction. Correlates of desiring a pregnancy within the next 6 months, and dual method use [defined as consistent condom use together with a highly effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 40 publications
(72 reference statements)
4
34
2
1
Order By: Relevance
“…For PLWH with a partner living without HIV or HIV unknown status partner, one study revealed that 44% of the participants desired for child in future. Lastly, among PLWH with a partner with unknown HIV status, a wider range of percentages was observed in the four studies, varying from 8% to 63% .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For PLWH with a partner living without HIV or HIV unknown status partner, one study revealed that 44% of the participants desired for child in future. Lastly, among PLWH with a partner with unknown HIV status, a wider range of percentages was observed in the four studies, varying from 8% to 63% .…”
Section: Resultsmentioning
confidence: 87%
“…Concerning PLWH, studies conducted after the introduction of combination therapies in 1996 have suggested that a substantial proportion would like/expect to have children. However, this prevalence varied greatly by country and by study [24][25][26].…”
mentioning
confidence: 99%
“…Although these findings are not surprising [28,29], the decreasing trend in condom use both alone and in conjunction with other more effective contraceptive methods is concerning. The EMR routinely prompts health providers to offer condoms to all adults in ART clinics, yet despite these attempts, the use of condoms in combination with other contraceptives remains low.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, dual method use in most sub-Saharan settings is low. 21,28 A recent study in Namibia, Kenya and Tanzania observed low dual method use and low use of highly effective contraception among people living with HIV for whom contraceptive protection was predominantly through condom-only use. 28 Dual contraceptive use in Kenya is very low as some couples believe it is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…21,28 A recent study in Namibia, Kenya and Tanzania observed low dual method use and low use of highly effective contraception among people living with HIV for whom contraceptive protection was predominantly through condom-only use. 28 Dual contraceptive use in Kenya is very low as some couples believe it is unnecessary. 29 Ralph et al 9 highlighted the need for future priorities to include expanding contraceptive choice and identifying effective ways of promoting use of dual methods.…”
Section: Discussionmentioning
confidence: 99%